IEEE Proceedings. VR 2005. Virtual Reality, 2005.
DOI: 10.1109/vr.2005.1492771
|View full text |Cite
|
Sign up to set email alerts
|

Immersiveness and symmetry in copresent scenarios

Abstract: Collaboration at a distance has long been a research goal of distributed virtual environments. A number of recent technologies, including immersive projection technology systems (IPTs) and head-mounted displays (HMDs), promise a new generation of technologies that are more intuitive to use than desktop-based systems.This paper presents an experiment that compares collaboration in five different settings. Pairs collaborated on the same puzzle-solving task using one of: an IPT connected to another IPT, an IPT co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Further results demonstrated the benefits of using immersive technologies, and showed the advantages of using symmetrical settings for better performance (see Figure 2). During earlier studies [30] we observed that some concrete factors, like presence and performance could be quantitatively approached in the environments, but to understand collaboration the quantitative evaluations were not enough [9]. In a later study adding qualitative evaluations showed more benefits, e.g.…”
Section: Previous Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Further results demonstrated the benefits of using immersive technologies, and showed the advantages of using symmetrical settings for better performance (see Figure 2). During earlier studies [30] we observed that some concrete factors, like presence and performance could be quantitatively approached in the environments, but to understand collaboration the quantitative evaluations were not enough [9]. In a later study adding qualitative evaluations showed more benefits, e.g.…”
Section: Previous Studiesmentioning
confidence: 95%
“…Details on networked experiments can be founded in Heldal et al [9] For the collaborative settings, see Table 1. For face-to-face collaboration with real objects, see Figure 1.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these approaches use a common fixed PoV or are based on deformation of the projection . In case of shared space among different users, it is possible to adopt a technique that privileges a specific user, for example, according to his or her role in an interactive task . The selection of a specific technique depends on the application, and it is important to evaluate the techniques in terms of performance and consistency among the users' views .…”
Section: Introductionmentioning
confidence: 99%
“…Besides traditional gaming and entertainment applications, some serious propositions are starting to emerge for their use both in education (ReLive, 2008;de Freitas, 2008;Otto et al, 2006;Heldal et al, 2005;Daily et al, 2000) and in the corporate world (Bartholomew, 2008;IBM, 2010;Nguyen et al, 2008), particularly to foster remote collaboration within increasingly globally distributed institutions and industries. Industry forecasts (Driver and Driver, 2009) predict that within the next decade an immersive layer will be added to current web technology, providing a high-degree of integration between immersive technology and the web, and making virtual worlds a mainstream technology for business and education.…”
Section: Introductionmentioning
confidence: 99%